2020
DOI: 10.1093/ee/nvaa076
|View full text |Cite
|
Sign up to set email alerts
|

Colonization by Biological Control Agents on Post-Fire Regrowth of Invasive Lygodium microphyllum (Lygodiaceae)

Abstract: Abstract Integration of biological control with other management tactics such as prescribed burning is often important for successful invasive weed control. A critical step in this integration is determining whether the agent can colonize postburn growth of the weed. Here, we investigated postburn colonization by biological control agents on regrowth of the invasive vine Lygodium microphyllum (Cav.) R. Br. (Lygodiaceae, Old World climbing fern) in Florida. We mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, the Paperbark melaleuca biocontrol in particular is integrated into broader chemical and mechanical control of the species . Biological control of Old World climbing fern (David et al 2020(David et al , 2021 and Water hyacinth ) can also complement other control measures by attacking the regenerating plant following fire or chemical treatments. However, an ongoing challenge is uneven establishment of the agents.…”
Section: Biological Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Paperbark melaleuca biocontrol in particular is integrated into broader chemical and mechanical control of the species . Biological control of Old World climbing fern (David et al 2020(David et al , 2021 and Water hyacinth ) can also complement other control measures by attacking the regenerating plant following fire or chemical treatments. However, an ongoing challenge is uneven establishment of the agents.…”
Section: Biological Controlmentioning
confidence: 99%
“…However, an ongoing challenge is uneven establishment of the agents. For instance, climate, genetics, or soil conditions are thought to limit establishment of agents both within South Florida and more broadly into Central and North Florida (Center et al 2000, David et al 2020). These limitations may eventually be overcome by importing different biotypes of the same species [e.g., the importation of the Nepalese biotype of the Air potato beetle (Smith et al 2018)] or through the approval, release, and establishment of additional species of biological control agents.…”
Section: Biological Controlmentioning
confidence: 99%
“…Several biocontrol agents exist for Old World climbing fern, and recent research has shown that they can re-colonize burned climbing fern stands within five to nine months post fire, but also that Old World climbing fern could reach its original percent cover within just five months (David et al 2020). The authors suggest that leaving refugia of climbing fern (and hence the biocontrol agents) could help with post-burn recolonization and therefore provide a reduction in overall growth rates, but this has not yet been demonstrated, and more research is needed.…”
Section: How Climbing Ferns Respond To Firementioning
confidence: 99%
“…However Japanese climbing fern recovers more quickly, resulting in a shorter window of around 6 to 9 months to get benefits from its top kill (Carmichael 2012). Studies on Old World climbing fern indicate its window for control is 12 to 18 months post-fire, although one study observed full recovery in just 5 months (Richards, Sebesta, and Taylor 2020;Hutchinson 2010;David et al 2020).…”
Section: Management Implicationsmentioning
confidence: 99%
“…The pace of post-fire recolonization by herbivores will depend in part on the traits and life-history strategies of the individual herbivore species. Flighted, mobile species are likely to disperse more rapidly post-fire (Knight & Holt 2005;David et al 2020), though some flighted species still may take years to recolonize (e.g., some cynipid gall-wasps in Florida scrub, Cronin et al 2020). Additionally, dietary specialists recover slower than dietary generalists (García et al 2016;Koltz et al 2018;Bosc & Pauw 2020).…”
Section: Introductionmentioning
confidence: 99%